The place of the current holy places of worship (kojo-bilal, kojo-kair) in society (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
In the article, the place of pilgrimage in the community of holy places, including pilgrimage to the holy places of worship where the remains of Kojo and Eshen are located, is considered as an integral part of the Islamic religion, as well as the traditional culture of life of the Kyrgyz people in the southwest of the Fergana Valley.
Keywords: saint, pilgrimage, Kojo, Eshan, polytheism